EFFECTIVENESS OF VARIOUS COMMERCIAL EXTENDERS IN CRYOPRESERVING SEMEN OF LOCAL INDONESIAN RAMS - Setiadi, Dedi Rahmat; Magfira; Riwu, Ronny Markus Jami; Arifiantini, R Iis (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Indonesian local sheep represent a particular species of sheep reared by farmers on small-scale farms. Semen freezing can be performed using either a homemade or commercial extender. The present study evaluated the effectiveness of several commercial extenders in freezing Indonesian local sheep. Semen was collected from three mature and healthy rams using an artificial vagina and evaluated. It was determined that only samples exhibiting sperm motility levels of greater than 70% would be included in the study. Subsequently, the semen from each ram was divided into three portions and diluted with Andromed, Sterydil, and OptiXcell, respectively. The frozen semen was then evaluated 24 hours post-freezing. The thawing process was conducted individually at 37°C for 30 seconds. The evaluation encompassed a range of metrics, including sperm motility, viability, and the presence of any abnormalities, in addition to the recovery rate. The results indicated that sperm frozen in Optixcell and Sterydil extenders exhibited superior motility, viability, and recovery rate than Andromed. The study also demonstrated no interaction between individual Ram and extender, and no differences were found between individuals. The study concluded that Optixcell and Sterydil extenders effectively froze Indonesian local sheep semen.